Effect of azadirachtin and dihydro azadirachtin on invitro acquisition of rice tungro viruses - JASVIR SINGH, C.N. BIJU, F.R. NIAZI and (Indian Phytopathology, 2007)
Two new neem oil formulations of azadirachtin (AZA) and dihydro azadirachtin (DHA) were tested in membrane feeding system either by mixing or spraying the membranes to investigate their effect on survival and feeding behaviour of green leafhopper (Nephotettix virescens Distant) and also on in vitro acquisition of rice tungro viruses. Although both the formulations were found effective, DHA @ 2500 ppm provedto be the most effective (in both modes of treatment) in adversely affecting the vector survival, feeding behaviour and transmission of tungro viruses.